2020
DOI: 10.3390/ani10081291
|View full text |Cite
|
Sign up to set email alerts
|

The Stomach Capacity is Reduced in Intrauterine Growth Restricted Piglets Compared to Normal Piglets

Abstract: Selection for increased litter sizes have decreased the average birth weight of piglets and up to 30% of newborn piglets in Danish herds show signs of intrauterine growth restriction (IUGR). It has been reported that around 48% of liveborn piglets dying between birth and weaning have empty stomachs, and that IUGR piglets do not ingest the recommended amount of colostrum to survive. The aim of this study was to investigate how much colostrum could be administrated depending on whether they were IUGR compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…However, there are still some challenges that prevent animals to fully express their growth potential 1 . Among them, intrauterine growth restriction (IUGR) stands out as the main cause of low birth weight and postnatal impaired body growth, affecting up to 20% of piglets within a litter in modern hyperprolific sows 2 , 3 . It has been reported that IUGR has harmful impacts on neonatal survival, postnatal growth, nutrition utilization efficiency, health, and performance 2 , 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still some challenges that prevent animals to fully express their growth potential 1 . Among them, intrauterine growth restriction (IUGR) stands out as the main cause of low birth weight and postnatal impaired body growth, affecting up to 20% of piglets within a litter in modern hyperprolific sows 2 , 3 . It has been reported that IUGR has harmful impacts on neonatal survival, postnatal growth, nutrition utilization efficiency, health, and performance 2 , 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings agree with the work of Douglas et al [ 19 ], who showed that AC and birth weight were good predictors of performance. This is likely due to them being indicative of stomach capacity, which is greater in larger pigs allowing more milk and colostrum to be consumed at each let down [ 31 , 32 ]. Further, our second colostrum model supports this assumption as 24 h weight was a good measure of consumed colostrum when modelled with PigProp.…”
Section: Discussionmentioning
confidence: 99%
“…Amdi et al [17] identified a large variation in stomach weight and capacity in both IUGR and normal piglets at birth. Under artificial feeding conditions, the maximum capacity of a newborn IUGR piglet's stomach was ~50 mL per kg/BW [30]. This would require the feeding of colostrum at least 5 times within the first 24 h to achieve appropriate intake for improved survival.…”
Section: Colostrum Intakementioning
confidence: 99%